Region and the American Presidency: Jimmy Carter as the “Southern” President - Berggren, D. Jason (American Studies in Scandinavia, 2020)
This study is about region and the politics and political style of Jimmy Carter. In 1976, the former Georgia governor broke a regional barrier to become president of the United States. He was a white southerner from the Deep South. As a candidate, he regularly identified himself as being from the South and spoke with pride about his regional connections. Although being from the South may have had some political costs, Carter did not consider it a liability. It helped him win the Democratic Party nomination and the general election. It reinforced his image as a Washington outsider. Indeed, had it not been for the near solid support from his home region in the Electoral College, he would have lost to Gerald Ford. Carter was also a southern president. He used his regional identity to establish and maintain relations with other Americans and with international leaders. He employed it in domestic and foreign policy situations, most notably in his efforts to advance Middle East peace.